2010
DOI: 10.1099/mic.0.034058-0
|View full text |Cite
|
Sign up to set email alerts
|

Ensifer, Phyllobacterium and Rhizobium species occupy nodules of Medicago sativa (alfalfa) and Melilotus alba (sweet clover) grown at a Canadian site without a history of cultivation

Abstract: Phage-resistant and -susceptible bacteria from nodules of alfalfa and sweet clover, grown at a site without a known history of cultivation, were identified as diverse genotypes of Ensifer, Rhizobium and Phyllobacterium species based on sequence analysis of ribosomal (16S and 23S rRNA) and protein-encoding (atpD and recA) genes, Southern hybridization/RFLP and a range of phenotypic characteristics. Among phage-resistant bacteria, one genotype of Rhizobium sp. predominated on alfalfa (frequency~68 %) but was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 38 publications
2
61
0
6
Order By: Relevance
“…Phyllobacterium strains have been identified in different environments (31), mostly as plant-associated bacteria (28,30,47,48). To date, the Phyllobacterium genus contains 10 species, but only two, P. trifolii and P. sophorae, are able to induce effective nodules on their host legumes, Trifolium pratense and Sophora flavescens, respectively (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Phyllobacterium strains have been identified in different environments (31), mostly as plant-associated bacteria (28,30,47,48). To date, the Phyllobacterium genus contains 10 species, but only two, P. trifolii and P. sophorae, are able to induce effective nodules on their host legumes, Trifolium pratense and Sophora flavescens, respectively (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported the isolation and characterization of phages of Rhizobium, including their role in Rhizobium ecology (11,13,19,39,40). Generally, phages have been used for typing Rhizobium strains as indicators of diversity and symbiotic performance (39)(40)(41)(42). They have also been useful as genetic tools to construct linkage maps for the chromosome and to allocate nitrogen fixation and nodulation loci in plasmids (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Todos los aislados autóctonos presentaron altos niveles de resistencia intrínseca a los antibió-ticos, particularidad que también fue señalada por Bromfield et al (2010) para especies del género Rhizobium, Ensifer y Phyllobacterium. Según Jordán (1984), la mayor susceptibilidad es característica del género Rhizobium a diferencia de las cepas de crecimiento lento del género Bradyrhizobium, las cuales han mostrado un espectro más amplio de resistencia a los antibióticos en cuanto al número y concentraciones ensayadas.…”
Section: Discussionunclassified
“…Sin embargo, el perfil de restricción incluyó a Rm V en el grupo de S. americanum CFN-Ei 156 (100% similares) y a Rm B en un genotipo diferente con 80% de similaridad a las cepas de referencia de crecimiento rápido R. tropici CiAT 899 y S. americanum CFNEi 156. Estos resultados son apoyados por los encontrados por Bromfield et al (2010), quienes han señalado a Medicago sativa como una leguminosa, cuyos nódulos estaban ocupados por varios genotipos bacterianos, pertenecientes a los géneros Ensifer, Rhizobium y Phyllobacterium, este último considerado como oportunista.…”
Section: Discussionunclassified